2019
DOI: 10.1016/s1474-4422(19)30149-8
|View full text |Cite
|
Sign up to set email alerts
|

Stenting for symptomatic vertebral artery stenosis: a preplanned pooled individual patient data analysis

Abstract: Executive committeeA Algra, A Compter (trial coordinator), L J Kappelle (coprincipal investigator), W J Schonewille, and H B van der Worp (co-principal investigator). Data safety monitoring board M L Bots (chair, epidemiologist), L Defreyne (radiologist), and P J Koudstaal (neurologist). Outcome assessment committees E J van Dijk (neurologist), C J Frijns (neurologist), J Hofmeijer (neurologist), M A van Buchem (radiologist), D R Rutgers (radiologist), B K Velthuis (radiologist), and T D Witkamp (radiologist).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…All three cases of cerebral hemorrhage in the PTAS group occurred within 7 days after the surgery. In PTAS, the increased risk of rupture may be due to the following: (1) the thin wall of the intracranial arteries ( 21); (2) the intracranial arteries located in the cerebrospinal fluid of the subarachnoid cavity with no tissue around them; (3) the perforating arteries of the intracranial arteries and the possible damage of these arteries during stent placement (22); and (4) the experience of the operator is another important factor that affects the outcome of stent therapy. To reduce the risk of stroke recurrence or death, the technology needs to be improved based on the above characteristics in the future.…”
Section: Discussionmentioning
confidence: 99%
“…All three cases of cerebral hemorrhage in the PTAS group occurred within 7 days after the surgery. In PTAS, the increased risk of rupture may be due to the following: (1) the thin wall of the intracranial arteries ( 21); (2) the intracranial arteries located in the cerebrospinal fluid of the subarachnoid cavity with no tissue around them; (3) the perforating arteries of the intracranial arteries and the possible damage of these arteries during stent placement (22); and (4) the experience of the operator is another important factor that affects the outcome of stent therapy. To reduce the risk of stroke recurrence or death, the technology needs to be improved based on the above characteristics in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an analysis including data from SAMMP-RIS and from two more recent RCTs dedicated to vertebral artery stenosis (VAST and VIST) 14,13 did not show evidence of benefit in stroke prevention for either medical or endovascular treatment in SIVBS. 26 In point of fact, the number of patients with SIVBS who received endovascular treatment in these RCTs is low (only 36 patients in SAMMPRIS, 13 in VIST, and 9 in VAST). An analogous meta-analysis including 23 studies showed that risk of stroke recurrence or death is comparable between medical and endovascular treatment in patients with SIVBS.…”
Section: Patient Selectionmentioning
confidence: 93%
“…Similar or worse results have been reported by the meta-analysis by Markus et al and Abuzinadah et al: for posterior circulation intracranial stent placement, they reported a peri-procedural stroke and death rate of 16% and 6,5% respectively. 26,27…”
Section: Early Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to know whether endovascular therapy can reduce the risk of recurrent stroke. The role of angioplasty and stenting based on the stenosis diameter in the intracranial artery is unclear 4–7. A previous study showed that the stroke recurrence risk is associated with features of vulnerable plaque rather than the diameter of the stenosis 8.…”
Section: Introductionmentioning
confidence: 99%